Longitudinal match performance characteristics of UK and non-UK players in the English Premier League. Issue 1 (2nd January 2017) - Bush, Michael; Archer, David T; Barnes, Chris; Hogg, Bob; Bradley, Paul S
ABSTRACT: This study investigated the longitudinal match performance characteristics in the English Premier League (EPL), with special reference to player nationality (UK vs. non-UK). Match observations ( n  = 14700) were collected using a multi-camera computerised tracking system across 7 consecutive EPL seasons (2006–2007 to 2012–2013). Player nationality referred to their birthplace, with players born in England, Scotland, Wales or Northern Ireland classified as the UK players and other nationalities considered non-UK. The non-UK players demonstrated the most pronounced increases in high-intensity running distance across the 7 seasons compared with UK players ( P  < 0.001, ES: 0.91 vs. 0.73). The UK players covered more high-intensity running distance in 2006–2007 ( P  < 0.001, ES: 0.24 [CI 0.17–0.31]), however by 2012–2013 both populations covered similar distances ( P  > 0.05, ES: 0.08 [CI 0.01–0.15]). In contrast, the non-UK players performed more passes in 2006–2007 compared with the UK players ( P  < 0.001, ES: 0.23 [CI 0.16–0.3]), however by 2012–2013, passing performance between the UK and non-UK players was equal ( P  > 0.05, ES: 0.05 [CI −0.01–0.13]). The data demonstrates that the longitudinal match performance characteristics in the EPL are similar between the UK and non-UK populations.